If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 0)(x + -2) = 4 Reorder the terms: (0 + x)(x + -2) = 4 Remove the zero: (x)(x + -2) = 4 Reorder the terms: x(-2 + x) = 4 (-2 * x + x * x) = 4 (-2x + x2) = 4 Solving -2x + x2 = 4 Solving for variable 'x'. Reorder the terms: -4 + -2x + x2 = 4 + -4 Combine like terms: 4 + -4 = 0 -4 + -2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '4' to each side of the equation. -4 + -2x + 4 + x2 = 0 + 4 Reorder the terms: -4 + 4 + -2x + x2 = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -2x + x2 = 0 + 4 -2x + x2 = 0 + 4 Combine like terms: 0 + 4 = 4 -2x + x2 = 4 The x term is -2x. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2x + 1 + x2 = 4 + 1 Reorder the terms: 1 + -2x + x2 = 4 + 1 Combine like terms: 4 + 1 = 5 1 + -2x + x2 = 5 Factor a perfect square on the left side: (x + -1)(x + -1) = 5 Calculate the square root of the right side: 2.236067978 Break this problem into two subproblems by setting (x + -1) equal to 2.236067978 and -2.236067978.Subproblem 1
x + -1 = 2.236067978 Simplifying x + -1 = 2.236067978 Reorder the terms: -1 + x = 2.236067978 Solving -1 + x = 2.236067978 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 2.236067978 + 1 Combine like terms: -1 + 1 = 0 0 + x = 2.236067978 + 1 x = 2.236067978 + 1 Combine like terms: 2.236067978 + 1 = 3.236067978 x = 3.236067978 Simplifying x = 3.236067978Subproblem 2
x + -1 = -2.236067978 Simplifying x + -1 = -2.236067978 Reorder the terms: -1 + x = -2.236067978 Solving -1 + x = -2.236067978 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = -2.236067978 + 1 Combine like terms: -1 + 1 = 0 0 + x = -2.236067978 + 1 x = -2.236067978 + 1 Combine like terms: -2.236067978 + 1 = -1.236067978 x = -1.236067978 Simplifying x = -1.236067978Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.236067978, -1.236067978}
| 5280.1000= | | -x+5y=14 | | 12x/1=25 | | 6*2=7x+11 | | (4x+3)=(2x-7) | | 7(z-4)+7z-3= | | [(-2)+a]-2=-7 | | 75+20h=155 | | 7x/15-1=12 | | b*(-7)*(-4)=6 | | x/2+6=8 | | bx(-7)x(-4)=6 | | 14/2+3(5)= | | -16X^2+64X+512=0 | | 19=18-A | | y^3-36y+8(y+6)= | | y^3-28y+48= | | 4z+3=47 | | y-15=-15 | | B=9(3.14)f | | -x2/10+9x/10+11/5 | | (6g*x)(6g+3h)=36g^2-9h^2 | | -1/3(6h+15) | | (x-1)/(x^2+2x-3) | | -6/x^3*-2/x^3 | | (x+2)(x+2)=2x^2+2x-11 | | 19e-27e+36=76 | | 29+58= | | 3p+5q=-14 | | 5t-u+v=3 | | x^3-9x^2+3=0 | | 6/x-2/(x+3) |